1999
DOI: 10.1086/307093
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocentrifugally Driven Winds: Comparison of MHD Simulations with Theory

Abstract: Alfvén waves discovered by Hannes Alfvén (1942 Nature 150 405) are fundamental electromagnetic oscillations in magnetized plasmas existing in the nature and laboratories. Alfvén waves play important roles in the heating, stability and transport of plasmas. The anisotropic nearly incompressible shear Alfvén wave is particularly interesting since, in realistic non-uniform plasmas, its wave spectra consist of both the regular discrete and the singular continuous components. In this Alfvén lecture, I will discuss … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
190
4
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(208 citation statements)
references
References 39 publications
13
190
4
1
Order By: Relevance
“…Especially for low plasma-β this may result in a devastating artificial collimation-preventing any steady state to establish and artificially collimating the outflow increasingly thin with time. Ustyugova et al (1999) have performed a systematic study comparing different approaches for outflow conditions including a (toroidal) force-free condition j p ||B p = 0 and a more sophisticated version including an additional numerical factor that needs to be determined a posteriori. For the outflow conditions in our simulations we instead recover the magnetic field components by imposing constraints on the poloidal (j r = −∂ z B φ , j z = r −1 ∂ r rB φ ) and toroidal (j φ = ∂ z B r − ∂ r B z ) electric currents.…”
Section: Injection Boundary (Z Beg )mentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for low plasma-β this may result in a devastating artificial collimation-preventing any steady state to establish and artificially collimating the outflow increasingly thin with time. Ustyugova et al (1999) have performed a systematic study comparing different approaches for outflow conditions including a (toroidal) force-free condition j p ||B p = 0 and a more sophisticated version including an additional numerical factor that needs to be determined a posteriori. For the outflow conditions in our simulations we instead recover the magnetic field components by imposing constraints on the poloidal (j r = −∂ z B φ , j z = r −1 ∂ r rB φ ) and toroidal (j φ = ∂ z B r − ∂ r B z ) electric currents.…”
Section: Injection Boundary (Z Beg )mentioning
confidence: 99%
“…d Krasnopolsky et al (1999) prescribe mass flux with the choice (E φ , E r , s, ρ, v z ) and superslow injection. e Ustyugova et al (1999) prescribe density ρ instead of the vertical velocity v z (thus change from Ustyugova et al 1995). The injection speed is allowed to become supersonic which strictly speaking results in an underdetermined system.…”
Section: Appendix a Zero Current Boundarymentioning
confidence: 99%
“…Numerical studies to date have shown the development of magnetic power spectra dominated by the largest scales permitted, in local disk simulations (e.g., Hawley, Gammie, & Balbus 1995), and that magnetically driven winds may develop from both cold and hot disks (e.g., Shibata & Uchida 1986;Stone & Norman 1994;Stone & Pringle 2000), with dependence of the angular momentum loss rate on similar to analytic pre-E B dictions (Kudoh, Matsumoto, & Shibata 1998). Because the choice of numerical boundary conditions (particularly for ) B f may affect the solution at the largest scale (see, e.g., Ustyugova et al 1999), a very large dynamic range would be needed to assess the external magnetic torque.…”
Section: Disk Accretion and Black Hole Spin-down Times Comparedmentioning
confidence: 99%
“…Bell & Lucek 1995;Matsumoto et al . 1996;Ustyugova et al 1999). In star-forming regions, such as in NGC 1333, a large number of jets, apparently all pointing in di¬erent directions, are seen (Hodapp & Ladd 1995).…”
Section: Out°ows From Disc Dynamosmentioning
confidence: 99%